Ethnomedicine Education and Willingness to Pay for the Preservation of Traditional Medicine in Oenoni I Village, Kupang Regency (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
Ethnomedicine knowledge in Oenoni I Village, Kupang Regency, is currently facing the threat of extinction due to modernization, necessitating conservation strategies based on community engagement. This community service project aimed to educate the public on the benefits of local medicinal plants while measuring their Willingness to Pay (WTP) to support sustainable preservation efforts. The approach utilized participatory education and a health economics survey through the Contingent Valuation Method (CVM) involving 45 respondents. The results demonstrated a clear shift in knowledge levels, with the proportion of residents in the "Good" category jumping from 32.4% to 75.6% post-intervention. From an economic perspective, residents showed a tangible commitment with a WTP range between Rp5,000 and Rp20,000 per month. With an average WTP value of Rp12,500 per household, the potential aggregate economic value could reach Rp30,000,000 per year. Although only 35% of residents were willing to contribute financially, the majority (65%) preferred non-monetary contributions such as labor, seedlings, and land provision. This study concludes that integrating health education with economic valuation effectively fosters community independence in maintaining ethnomedicine through village "living pharmacies." Moving forward, the program recommends establishing village-based enterprises to ensure both economic value and the legal safety of the herbal products produced.